MENTAL HEALTH PROFESSIONALS’ NON-CLINICAL ROLES AS INFORMED BY ATTACHMENT: A SYSTEMATIC REVIEW OF RESEARCH - Jennifer L Tipton; Casey A Barrio Minton; Brittney N. R. Irion (Teaching and Supervision in Counseling, 2025)
While attachment informs the quality of the therapeutic relationship, which is the basis of all therapeutic work for professional counselors and related mental health professionals (MHPs), less attention has been given to the role of attachment in MHPs’ non-therapeutic roles such as engagement in professional development, teaching, and supervision. This systematic review analyzed 33 research studies that investigated MHPs’ attachment in the context of non-therapeutic roles, including professional development, supervision, and teaching. Findings are discussed in the context of four emergent themes: Professional Functioning and Well-being, Supervisory Relationships, Self-awareness, and Empathy. There is considerable evidence that MHP attachment style is relevant across professional roles. Findings are discussed, implications for counselor education and supervision practice are identified, and recommendations for additional research are provided.
Keywords: Attachment; Clinical Supervision; Counselor Education; Empathy; Therapeutic Relationship